An Innovative Undergraduate Interdisciplinary Research Course: Development, Implementation, and Student Perspectives. Issue 10 (October 2021) - Vaughn, Jacqueline; Kamkhoad, Donruedee; Ford, Shannon; Subramaniam, Arvind P.; Khairat, Saif; Shah, Nirmish
Abstract : Supplemental digital content is available in the text.